2011 14th International IEEE Conference on Intelligent Transportation Systems (ITSC) 2011
DOI: 10.1109/itsc.2011.6082907
|View full text |Cite
|
Sign up to set email alerts
|

Drowsiness monitoring based on driver and driving data fusion

Abstract: This paper presents a non-intrusive approach for monitoring driver drowsiness, based on driver and driving data fusion. The Percentage of Eye Closure (PERCLOS) is used to estimate the driver's state. The PERCLOS is computed on real time using a stereo vision-based system. The driving information used is the lateral position, the steering wheel angle and the heading error provided by the CAN bus. These three signals have been studied in the time and frequency domain. A multilayer perceptron neural network has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 21 publications
0
38
0
2
Order By: Relevance
“…After some time, the driver recovered to an alert state with an acceptable lateral offset of the vehicle. Comparing with several other studies, Daza et al (2011) proposed a two-layered feed-forward artificial neural network to fuse the driver and driving data, obtaining a 98.65% drowsiness detection rate but only in a binary classification (awake and drowsy). Friedrichs and Yang (2010b) employed the Bayes classifier with the sequential floating forward selection (SFFS) algorithm and neural network to classify the driver's awake or drowsy states based on lane data and CAN data with test errors of about 36.6% and 16.6%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After some time, the driver recovered to an alert state with an acceptable lateral offset of the vehicle. Comparing with several other studies, Daza et al (2011) proposed a two-layered feed-forward artificial neural network to fuse the driver and driving data, obtaining a 98.65% drowsiness detection rate but only in a binary classification (awake and drowsy). Friedrichs and Yang (2010b) employed the Bayes classifier with the sequential floating forward selection (SFFS) algorithm and neural network to classify the driver's awake or drowsy states based on lane data and CAN data with test errors of about 36.6% and 16.6%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…LATSD reflects the volatility of the car's position at intervals. It has been proven to detect driver drowsiness at a rate of more than 80% in the study by Daza et al (2011). Features fusion. Rombaut (1998) has stated that the fusion of different features is based on the concept that a source cannot simultaneously affect mass on a hypothesis and its complementary, thus giving antagonistic information.…”
Section: Application To Drowsiness Estimationmentioning
confidence: 99%
“…It showed that the SVM classifier could differentiate the drowsiness and alertness states in an accuracy value of 99.3 %, so the ITR would be 5.64 bits/min. In [21], different features extracted from the states of the driver or the driving such as PERcentage of Eye Closure (PERCLOS), standard deviation and mean of the lateral position truck and wheel angle and heading error using the artificial neural network for classification are considered. It showed that the detection rate of drowsiness with the combination of these indicators (features) was 94 % in a temporal window of 20 s, so the ITR is 2.05 bits/min.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that a good strategy is to combine the detection of drowsiness with giving the driver feedback about his driving performance. In [4][5][6][7], they studied various analyses and methods of vehicle's behavior for detecting driver drowsiness using steering-related information and lane-related information.…”
Section: A Related Workmentioning
confidence: 99%